Impact of Board Diversity on Corporate Social Responsibility (CSR) on Malaysian Public Listed Companies - Suzila, Binti Mohamed Yusof; Salawati, Binti Sahari; Jais, Bin Mohamad (Human Resource Management Academic Research Society, 2019)
Different theories and empirical research have been done and suggested to define and clarify how board diversity give impacts to corporate social responsibility (CSR). This study examines the impact of board diversity towards CSR based on the 50 Malaysian Public Listed Companies within the year 2010 to 2016. Board diversity examines the board gender, board age, board size, board independence and board tenure toward CSR. The methodology of the study used Ordinary Least Square (OLS) regression to determine the relationship of CSR and all variables under the board diversity. Various analysis being done starting from the Pearson Correlation Coefficient Test and Descriptive Statistics Analysis. Model determination in this study also being analysed by using The Breusch & Pagan Lagrange Multiplier (LM Test) and Hausman Test. Based on the findings, the regression results show the diversification of the board, and other control variables had a positive relationship with CSR. The results revealed that the impact of board diversity gives positive relationship towards the CSR performance among the companies except for board tenure that brings negative relationship towards CSR performance.